Semiotic of Sign and Plot in The Eternal Sunshine of The Spotless Mind. - Reynaldi, Muhammad Iqbal Nurcahyo (Universitas Negeri Surabaya, 2022)
This research study discussed signs in the movie The Eternal Sunshine of The Spotless Mind by Michel Gondry that shown in the character's hair affected the plot of the movie. The story is based on the character's relationship named, Joel and Clementine; the movie's point of view is from Joel's perfective, and the sign is shown in Clementine's hair color. Using Roland Barthes's theory of semiotic analysis of signs to analyze Clementine's hair color impacted the plot of the movie. The writer use the denotation and connotation levels Based on the sign shown in the movie to explain the meaning of the hair color. The writer understands that colors have meaning that has an impact on the movie and the plot. In addition the movie was not used general order plot, By applying the semiotic of sign theory by Roland Barthes, the writer concludes that Clementine's hair had color correlates with the plot of the movie.